Temperature-dependent functional response of Euborellia annulipes (Dermaptera: Anisolabididae) preying on Plutella xylostella (Lepidoptera: Plutellidae) larvae - Nunes, Gilmar da Silva [UNESP] (2020)
Temperature mediates trophic interactions, including relationships between insect pests and predators, and functional response studies are often used to determine the suitability of predators as biocontrol agents. We investigated the effects of temperature on the functional response of Euborellia annulipes (Lucas) (Dermaptera: Anisolabididae) preying on Plutella xylostella (L.) (Lepidoptera: Plutellidae) larvae. Predation rate, type of functional response, attack rate (a'), handling time (T-h), and maximum predation rate (T/T-h) of the predator were estimated using seven prey densities and three thermal conditions. The functional response of E. annulipes to P. xylostella was temperature-dependent, type III under the lower temperatur (18 degrees C and 25 degrees C), and type II at 32 degrees C. We observed increasing values of a' in 25 degrees C and 32 degrees C, decreasing values of Th and highest T/T-h as the thermal condition increased. Our findings suggest that E. annulipes could be effective to control P. xylostella under different thermal conditions, however its predation behavior changes according to temperature variation.